Analysis of the Financial Performance of Manufacturing Companies in the Cigarette Sub-Sector of the Consumer Goods Industry - Muhamad Yamin Noch; Mohamad Ridwan Rumasukun; Ronald Sinyo Noriwary; Victor Pattiasina (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2023)
The purpose of conducting research is to analyze the financial performance of cigarette companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019 through analysis of liquidity, solvency, activity, and profitability ratios. The research data is secondary data obtained indirectly from third parties or through documents. The data source for this research was obtained from the internet via the official website of the Indonesia Stock Exchange (IDX), www.idx.co.id, in the form of annual reports of companies in the cigarette sector in the consumer goods industry for 2016-2019. The results showed that the company Gudang Garam Tbk had excellent performance; this was evidenced by the liquidity, solvency ratio, activity ratio, and the company's profitability ratio, which continued to fluctuate and tended to increase. The company H. M Sampoerna Tbk has performed exceptionally well, evidenced by the ratio of liquidity and solvency, and is terrible when judged by the ratio of activity and profitability. The company Bentoel International Investama has a poor performance, evidenced by its profitability ratio, which experiences losses yearly, but the ratio of liquidity, solvency, and activity fluctuates. PT. Wismilak Inti Makmur has performed exceptionally well, judging from its liquidity, solvency, and profitability ratios. However, in terms of its activity ratio, it has performed quite poorly because its value continues to decline.Keywords:Liquidity Ratio; Solvency Ratio; Activity Ratio; Profitability Ratio